2016
DOI: 10.5812/archcid.34806
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection and Risk of Breast Cancer: An Adaptive Meta-Analysis for Case-Control Studies

Abstract: Context: The association between 'Epstein-Barr' virus (EBV) and breast cancer risk still remains controversial. A Systemic Review (SR) published in 2012 reported that there might be a statistically significant association between EBV and risk of breast cancer. However, errors were found in the appraisal process of the concerned SR. Objectives:The aim of this report was to conduct an adaptive meta-analysis with additional extraction of relevant papers published up until September 2015.Data Sources: The lists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
3
4
0
Order By: Relevance
“…In this case-control study, EBV-DNA positivity increased the risk of BC development by about threefold (OR = 3.05). This is similar to two recent meta-analysis that reported that the risk of BC association with EBV infection is 3.84 and 4.74 folds higher as compared to controls (Bae and Kim, 2016;Farahmand et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In this case-control study, EBV-DNA positivity increased the risk of BC development by about threefold (OR = 3.05). This is similar to two recent meta-analysis that reported that the risk of BC association with EBV infection is 3.84 and 4.74 folds higher as compared to controls (Bae and Kim, 2016;Farahmand et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The exact role that EBV plays in the promotion of benign tumours, and the progression of breast cancer in women is still uncertain, despite several studies showing an association between the virus and this type of malignancy (11). A meta-epidemiological study concluded that EBV infection may increase the risk of breast cancer (1). EBV is known by its capacity to induce cellular growth and alter the tumoural environment (24).…”
Section: Discussionmentioning
confidence: 99%
“…Association between EBV and breast cancer have been reported from different parts of the world including Asia [188], Africa [189], and Europe [190], with a prevalence of 30-50%. Subsequently, EBV latency II gene products such as LMP-1, -2, EBNA-, and EBER have been detected in breast cancer cells [102,191,192], and a meta-epidemiological study have also shown that EBV infection was highly associated with the risk of breast cancer development [193].…”
Section: Breast Cancermentioning
confidence: 99%